Réponses

Meilleure réponse !
2013-05-14T20:55:32+02:00

3(2x+3)

2(2x+4)

3(2x+1)

4(x-4)

5(x-3)

3(x-2)

2013-05-14T20:59:21+02:00

6x + 9 = 3 * 2x + 3 * 3

            = 3 ( 2x + 3 )

 

4x + 8 = 4 * x + 4 * 2

            = 4 ( x + 2 )

 

6x + 3 = 3 * 2x + 3 x 1

            = 3 ( 2x + 1 )

 

4x - 16 = 4 * x - 4 * 4

             = 4 ( x - 4 )

 

5x - 15 = 5 * x - 5 * 3

             = 5 ( x - 3 )

 

3x - 6 = 3 * x - 3 * 2

           = 3 ( x - 2 ).

 

 

 

Voilààà. 

Si tu as besoin d'explications, dis-le ;).